ANALISIS PERMINTAAN DAN FAKTOR-FAKTOR YANG MEMPENGARUHI PERMINTAAN BUAH JERUK LUMAJANG DI KABUPATEN GIANYAR - Komang Ayu Tri Puspa Rini; I Made Budiasa; Cening Kardi , (AGRIFARM (Jurnal Agribisnis dan Sosial Ekonomi Pertanian), 2023)
Oranges are one of the fruit commodities that have an important role in the world market as well as in the country. The purpose of this study is to determine the function and elasticity of demand and the factors that influence the demand for Lumajang oranges in Gianyar Regency. Determination of the research location is done by purposive sampling method based on several considerations. This research was conducted from October 2022 to November 2022. Determination of the number of samples for consumers of lumajang oranges was carried out using the accidental sampling method which was determined by 30 respondents. The data analysis method used in this research is Cobb-Douglas analysis. The results of this study indicate that the demand function for lumajang oranges is Qd=10,064X1-0,103X20,524X30,241X40,505X50,116 with the price elasticity of lumajang oranges being inelastic. Meanwhile, the t-test shows that the factors that influence the demand for lumajang oranges in the Gianyar Public Market are the price of green apples, the price of salak, and income have a positive and significant effect on the demand for lumajang oranges, while the price of lumajang oranges has a negative effect, while education is not significantly different